2008
DOI: 10.1093/molehr/gam088
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in cumulus cells as a prognostic indicator of embryo viability: a microarray analysis

Abstract: Besides the established selection criteria based on embryo morphology and blastomere number, new parameters for embryo viability are needed to improve the clinical outcome of IVF and more particular of elective single-embryo transfer. Genome-wide gene expression in cumulus cells was studied, since these cells surround the oocyte inside the follicle and therefore possibly reflect oocyte developmental potential. Early cleavage (EC) was chosen as a parameter for embryo viability. Gene expression in cumulus cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(105 citation statements)
references
References 71 publications
7
92
0
4
Order By: Relevance
“…The expression of Kit, which marks the germ cells prior to preleptotene [29], did not exhibit significantly different expression patterns either. The expression of Ldhc4, a gene restricted to the mid/late-pachytene spermatocytes [30], was markedly increased in the transgenic mice testes, whereas the expression of Dvl1, a gene activated in round, elongating, and elongated spermatids [31,32], tended to be far weaker in the transgenic mice testes, consistent with our morphological observations. These observations confirm that transgenic mice fail to complete spermatogenesis, the process being specifically arrested at the stage of pachytene spermatocytes.…”
Section: Alr Transgenic Mice Showed a Range Of Abnormal Spermatogenesissupporting
confidence: 89%
“…The expression of Kit, which marks the germ cells prior to preleptotene [29], did not exhibit significantly different expression patterns either. The expression of Ldhc4, a gene restricted to the mid/late-pachytene spermatocytes [30], was markedly increased in the transgenic mice testes, whereas the expression of Dvl1, a gene activated in round, elongating, and elongated spermatids [31,32], tended to be far weaker in the transgenic mice testes, consistent with our morphological observations. These observations confirm that transgenic mice fail to complete spermatogenesis, the process being specifically arrested at the stage of pachytene spermatocytes.…”
Section: Alr Transgenic Mice Showed a Range Of Abnormal Spermatogenesissupporting
confidence: 89%
“…1). Moreover, expression of apoptosis-related genes in CCs reported herein was also associated with oocyte final maturation progression in several previous studies in many mammalian species (Host et al 2002, van Montfoort et al 2008, and it was even suggested as an indicator to predict human oocyte quality (Lee et al 2001). However, at this stage (GVBD), the CCs tissue maintains a proliferative phenotype (cell cycle and cellular growth functions) that prepares the prerequisite structure for rapid expansion and oocyte competence acquisition support.…”
Section: Cellular and Molecular Function Analysissupporting
confidence: 55%
“…GPX3 catalyzes the reduction of free hydrogen peroxide, organic hydroperoxide and lipid peroxides and protects cells against oxidative damage [39]. GPX3 has also been proposed to be a marker of poor embryo quality as it was down-regulated in CC of early-cleaving embryos and up-regulated in CC of nonearly cleaving embryos [40]. Glutathione (GSH) function in oocytes is mainly related to antioxidative properties [41] furthermore, it protects the oocyte's meiotic spindle against oxidative damage [42].…”
Section: Discussionmentioning
confidence: 99%